2005
DOI: 10.1037/0735-7028.36.4.376
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Play Therapy With Children: A Meta-Analytic Review of Treatment Outcomes.

Abstract: The efficacy of psychological interventions for children has long been debated among mental health professionals; however, only recently has this issue received national attention, with the U.S. Public Health Service (2000) emphasizing the critical need for early intervention and empirically validated treatments tailored to children's maturational needs. Play therapy is a developmentally responsive intervention widely used by child therapists but often criticized for lacking an adequate research base to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
595
3
18

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 633 publications
(669 citation statements)
references
References 49 publications
31
595
3
18
Order By: Relevance
“…Ray (2006) provided a more updated review of play therapy research, again showing its effectiveness with a variety of issues and populations. Bratton, Ray, Rhine, and Jones (2005) conducted a meta-analysis of 93 controlled play therapy outcome studies involving children and found an overall treatment effect of .80 standard deviations, considered a large effect (Cohen, 1988). This finding indicates that after receiving play therapy, children performed .80 standard deviations above children who did not receive play therapy.…”
Section: Play Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…Ray (2006) provided a more updated review of play therapy research, again showing its effectiveness with a variety of issues and populations. Bratton, Ray, Rhine, and Jones (2005) conducted a meta-analysis of 93 controlled play therapy outcome studies involving children and found an overall treatment effect of .80 standard deviations, considered a large effect (Cohen, 1988). This finding indicates that after receiving play therapy, children performed .80 standard deviations above children who did not receive play therapy.…”
Section: Play Therapymentioning
confidence: 95%
“…Most CCPT therapists strongly agree that child mental health service personnel need to be responsive to the developmental level of children in both assessment and in treatment (Bratton, et al, 2008;Bratton, et al, 2005). Many experts in trauma believe a reciprocal relationship exists between trauma and a child's developmental level (James, 1989;van der Kolk, 1994;Shelby, 1999;Shelby & Felix, 2005).…”
Section: Trauma Within a Developmental Frameworkmentioning
confidence: 99%
“…This treatment, which originated with Anna Freud and Melanie Klein, and was subsequently developed by Axline, Landreth and others, uses play as the primary way in which a child expresses him/herself and communicates with the therapist [1]. From this perspective, in the context of a safe therapeutic relationship, during play with the therapist children express their feelings and learn more adaptive strategies to manage their distress and improve their level of functioning [1].…”
Section: Editorialmentioning
confidence: 99%
“…In a well-known study by Bratton, Ray, Rhine, and Jones (2005), the researchers concluded that CPRT had an effect size of 1.25, making it one of the most effective forms of treatment in the child psychotherapy field. CPRT has been associated with decreases in internalizing and externalizing behavior problems, and facilitation of academic success (Landreth & Bratton, 2006).…”
Section: Child؊parent Relationship Therapymentioning
confidence: 99%